Functional Outcomes of Pediatric Both Bone Fractures Fixed with Titanium Elastic Nails: A Hospital Based Study - KC, Kapil Mani; RC, Dirgha Raj; Acharya, Parimal; Sigdel, Arun; Lamal, Dinesh Kumar; Dahal, Sudip Chandra (Europasian Journal of Medical Sciences, 2021)
Background: Successful treatment of both bone fractures depends on the restoration of normal alignment and full recovery of range of motion that can be achieved by either closed reduction and casting or surgical intervention. Number of surgical treatment modalities have been mentioned for unstable pediatric both bone fractures that includes Kirschner wire fixation, plating, external fixation and elastic intramedullary nailing. Methods: This was descriptive cross-sectional study performed from January 2016 to December 2019. A total of 85 diaphyseal pediatric forearm fractures were treated surgically with titanium elastic nails(TENs) during this period. Functional outcomes and complications were analysed 6 months after surgery. Results: The mean age of patients in our study was 10.67±1.88. There were 50 (64.1%) male and 28 (35.9%) female. Incidence of fracture is higher in left side 47 (60.2%) in comparison to right side 31 (39.8%). Fifty (64.1%) fractures were in middle third, thirteen (16.7%) fractures were in proximal third and 15 (19.2%) in distal third of both bone forearm. There were excellent outcomes in 91%, good outcomes in 6.4% and fair results in only 2.6% of patients.Seven different types of complications were noted including skin irritation 8 (10.2%), cortex perforation in 2 (2.5%) and iatrogenic fracture in 1 (1.3%) case. Conclusions: Titanium elastic nailing is excellent treatment option for displaced unstable pediatric both bone fractures especially in elderly children. This is technically easy, minimally invasive procedure with relatively faster bone healing, easy implant removal with excellent cosmesis of skin without long ugly scar.